Suitability of Rubber Plantation Land Intercropped with Corn (Zea mays L) Plants in Betung Village of Banyuasin District - Yuana Juwita; Joni Karman; Yanter Hutapea; Suparwoto Suparwoto (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2020)
Juwita Y, Karman J, Hutapea Y, Suparwoto S. 2020. Suitability of rubber plantation land intercropped with corn (Zea mays L) plants in Kelurahan Betung. Jurnal Lahan Suboptimal: Journal of Suboptimal LandsÂ 9(1): 73-79.Rubber is one of the leading commodities of plantations in South Sumatra, especially in Banyuasin District. The opportunity for unused footpath land is a big potential in increasing farmers' income. In Betung Village, besides rubber, the community also raises livestock such as cows. This study aimed to provide information on the actual soil fertility status and see the suitability of the land in the study area when planted with corn plants, as well as the recommendations for the needed technology. The study used a survey method and the soil samples were taken using purposive random sampling method by determining the point diagonally and analyzed in the laboratory. The results of the study showed that the land suitability class at the location was according to the marginal with the limiting factors of water availability (rainfall) and nutrient retention (KB and pH). To obtain optimal corn production results, it is recommended to prepare a rainwater collection area and the addition of lime and organic matter.